2018
DOI: 10.3390/infrastructures3030017
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Materials for Transportation Infrastructures: Comparison of Three Commercially-Available Metakaolin Products in Binary Cementitious Systems

Abstract: Abstract:Metakaolin is the only major natural pozzolan to be specified for use as a supplementary cementitious material in the United States. As a result, the metakaolin market for concrete has grown dramatically in the past 20 years. As of now, the specifications of up to 16 state departments of transportation allow for the use of commercially-available and high-reactivity metakaolin products. However, to the best of the authors' knowledge, no study has been performed to evaluate whether these products are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…It was concluded that flash-calcined clays improve workability, porosity, and creeping. Similar conclusions were stated by Sullivan et al [ 36 ], showing that MK contributes to prolonging the service life of infrastructures. Danilevich et al [ 37 ] activated thermally aluminum hydroxide in gibbsite using a reactor called TSEFLAR.…”
Section: Introductionsupporting
confidence: 91%
“…It was concluded that flash-calcined clays improve workability, porosity, and creeping. Similar conclusions were stated by Sullivan et al [ 36 ], showing that MK contributes to prolonging the service life of infrastructures. Danilevich et al [ 37 ] activated thermally aluminum hydroxide in gibbsite using a reactor called TSEFLAR.…”
Section: Introductionsupporting
confidence: 91%
“…Previous studies have shown that increased SiO2 contents are expected when kaolin transforms into MK through heat treatment. The SiO2 contents can vary from 50 to 60%, sometimes reaching 74.3% (Fadzil et al, 2017;Pillay et al, 2020;Rashad, 2013;Sullivan et al, 2018). The remainder consists of kaolinite and a small amount of muscovite.…”
Section: Crystallinity and Functional Groupsmentioning
confidence: 99%
“…As such, metakaolin, which is basically made from kaolin (a type of clay) treated using a high calcination temperature [ 18 , 19 ], is considered to be one of the possible replacement materials. In spite of the calcination process necessary in metakaolin production, Sullivan et al [ 20 ], who reviewed the study by Selmani et al [ 21 ], stated that the manufacture of metakaolin involved much lower calcining temperatures and emitted less carbon dioxide than Portland cement. Therefore, metakaolin is gaining popularity in various construction applications, as mentioned in other studies [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%